Allium kubeysdaghense, A New Species of Allium sect. Codonoprasum (Amaryllidaceae) From Eastern Anatolia, Türkiye - Sonay, Veysel; Gül, Emel; Balos, Mehmet Maruf; Bagcı, Eyup (Uğur ÇAKILCIOĞLU, 2024)
Allium kubeysdaghense Balos & Sonay, Allium sect. a new species from Codonoprasum, described from Elazığ Province, eastern Turkey. It is morphologically similar to A. turcicum and A. turcicum subsp. fusciflorum in general shape and presence of long spathe valves. But it differs in papyrus-like outer tunic; flexible, purple or green petioles on the upper part of the leaves; leaf sheaths covering up to 2/3 of the total length of the scape; crescent-shaped leaf cross-section; leaf margins with 3 to 6 scabrous teeth; verrucose leaf surface; non waxy, cream or white bell-shaped perigone; different structure and shape of inner and outer tepals; reticulate ovary surface. This study includes a detailed description of the new species, photographs of the species, habitat and ecological characteristics, conservation assessment, significant morphological differences with related species, and seed micromorphology (SEM).
Keywords: Botany (Other); Bitki Bilimi (Diğer)